2007
DOI: 10.1073/pnas.0703333104
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the biodiversity value of tropical primary, secondary, and plantation forests

Abstract: Biodiversity loss from deforestation may be partly offset by the expansion of secondary forests and plantation forestry in the tropics. However, our current knowledge of the value of these habitats for biodiversity conservation is limited to very few taxa, and many studies are severely confounded by methodological shortcomings. We examined the conservation value of tropical primary, secondary, and plantation forests for 15 taxonomic groups using a robust and replicated sample design that minimized edge effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

43
814
4
47

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,003 publications
(908 citation statements)
references
References 24 publications
43
814
4
47
Order By: Relevance
“…However, this research suggests that maintaining a mosaic of habitats within managed commercial forests could benefit smooth snake populations. Although plantation forests are not able to support the biodiversity of primary habitats, they can have a role in complementary conservation services (Barlow et al, 2007). Further research concentrating on determining the precise stage at which young forestry stands may become unsuitable habitat for smooth snakes should be seen as a priority for forest management practices.…”
Section: Discussionmentioning
confidence: 99%
“…However, this research suggests that maintaining a mosaic of habitats within managed commercial forests could benefit smooth snake populations. Although plantation forests are not able to support the biodiversity of primary habitats, they can have a role in complementary conservation services (Barlow et al, 2007). Further research concentrating on determining the precise stage at which young forestry stands may become unsuitable habitat for smooth snakes should be seen as a priority for forest management practices.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the protection of primary forests or forests in the more advanced stages of regeneration can be prioritized. This would have considerable impact on the conservation of the flora and the fauna, particularly tropical forests (BARLOW et al, 2007;GIBSON et al, 2011).…”
Section: Environmental Implications and Controversiesmentioning
confidence: 99%
“…Barlow et al, 2007). Over the last decades, many studies have revealed species loss and altered community composition in response to tropical forest degradation (Hill and Curran, 2003;Turner, 1996).…”
Section: Introductionmentioning
confidence: 99%